Mothering, Substance Use Disorders and Intergenerational Trauma Transmission: An Attachment-Based Perspective - Meulewaeter, Florien; De Pauw, Sarah S. W.; Vanderplasschen, Wouter (Frontiers in Psychiatry, 2019)
Background: A growing body of research underlines that interpersonal trauma in childhood can lead to heightened susceptibility for substance use disorders in later life. However, little research has been conducted on parenting experiences of mothers in recovery from substance use, taking into account their own upbringing as a child and the potential aftermath of interpersonal childhood trauma. Methods: Through in-depth semi-structured qualitative interviews, 23 mothers in recovery from substance use reflected on parenting experiences and parent-child bonding, related to both their children and their own parents. Interviews were transcribed verbatim and data were analyzed adopting thematic analysis. Results: Throughout the narratives, consequences of trauma on mothers sense of self and its subsequent impact on parenting arose as a salient theme. Five latent mechanisms/stages of intergenerational trauma transmission were identified: 1) interpersonal childhood trauma experiences in mothers; 2) trauma as a precursor for substance use initiation; 3) substance use as a (self-fooling) enabler of parental functioning; 4) continued substance use impacting parental functioning; and 5) dysfunctional parental functioning and its relational impact upon offspring. Discussion: Findings suggest disruptive attachment can be a vulnerability to addiction on the one hand, and an expression of underlying trauma on the other, hence serving as a covert phenomenon by which trauma can be transmitted across generations. Results indicate the need for preventive, attachment-based and trauma-sensitive interventions targeted at disrupting harmful intergenerational patterns.